Desenvolvimento de biossensores raciométricos bioluminescentes de ph e metais divalentes baseados na engenharia da região sensível ao pH nas luciferases de vagalumes - Gabriel, Gabriele Verônica de Mello (2017)
Bioluminescence, the emission of visible light by living organisms is widely used in biosensors. Firefly luciferases and genes are among the most used reporter gene in bioluminescent biosensors. Firefly luciferases are pH-sensitive, exhibiting a red shifted bioluminescence spectra on the presence of metals, high temperatures and acidic pH, being this last property considered unusual for the most analytical applications. Nowadays most luminescent biosensors to metals and pH are fluorescent, and few of them are ratiometric based on spectral changes. Bioluminescent biosensors despite been less common, have same advantages as low background and does not need UV light irradiation, bring no photodamage to the cell. The aim of this project was: (I) study the applicability of the use of Macrolampis sp2 firefly luciferase and other pH-sensitive luciferases as spectral intracellular ratiometric pH biosensor; (II) apply these pH ratiometric biosensors in mammalian cells to investigate its physiology in real time and (III) developing, by engineering the pH sensor region of Macrolampis sp2 firefly luciferase, a ratiometric biosensor specific to metals. We obtained a relation between the pH and the ratio of the bioluminescence at green and red region of the spectra, allowing estimate ratiometrically the intracellular pH of bacteria and mammalian cells. Besides that, we confirmed its use to cellular image of pH and observed that occurs an alkalinization of the cytosol and nucleus during cell division and apoptosis. We demonstrate the applicability of firefly luciferases, in special the luciferase of Macrolampis sp2, as a ratiometric biosensor to metals and intracellular pH. The existence of a linear relationship between the concentrations of metals like cadmium, mercury and zinc, and the ratio of the bioluminescence at green and red region of the spectra, allowed also estimate ratiometrically, for the first time, concentrations of metals less than 100 μM, enabling the use of firefly luciferases as bioavailability indicator to toxic and potential toxic metals.